Early-strength and rapid-hardening steel slag-based road grouting material and preparation method thereof
Through the multi-component synergistic effect and optimized preparation process of steel slag-based grouting materials, the problems of insufficient strength in the early stage and the long settling time are solved, early strength and fast hard performance are achieved, road structure stability and environmental protection benefits are improved, and steel slag resource utilization is promoted.
Patent Information
- Application Number
- CN202510762600.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2025-08-29
AI Technical Summary
The existing steel slag-based grouting materials are difficult to meet the engineering needs for rapid road treatment and reinforcement in terms of insufficient early strength and long settling time. In addition, free calcium oxide and other components in the steel slag may cause poor volume stability, resulting in cracking of the grouting layer and affecting the durability of the project.
The combination of steel slag, fluorine gypsum, slag powder, silicon fume, phosphogypsum, exciter, water reducing agent, expansion agent and filler is adopted to form a sulfate-aluminate composite excitation system through coordinated optimization of multi-stage activation and process. The alkalinity is accurately controlled with the exciter, ultrasonic homogeneity and high-speed shear dispersion are optimized, pore structure is optimized, and early strength and fast hardness are achieved.
It has achieved early strength, fast hardness, high stability and environmental friendliness of steel slag-based grouting materials, significantly improved road maintenance and reinforcement efficiency, reduced production costs, and promoted the resource utilization of industrial solid waste.
Smart Images

Figure BDA0005440669760000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to an early-strengthening and fast-hardening steel slag-based road grouting material and a preparation method thereof. Background Art
[0002] In road construction and maintenance, grouting technology, as an efficient reinforcement and repair method, is widely used to improve the bearing capacity and stability of road structures. Traditional grouting materials are mostly cement-based. However, with the continuous improvement of material performance requirements in road construction and maintenance and the strengthening of environmental awareness, traditional grouting materials have gradually exposed their limitations in terms of early strength and rapid hardening performance, cost-effectiveness, and resource recycling. Steel slag, a major industrial solid waste generated during the steelmaking process, contains active mineral phases such as dicalcium silicate and calcium aluminoferrite in its chemical composition. It has certain hydraulic activity and can be used as a cementitious material after proper treatment. The application of steel slag in road grouting materials can not only realize the resource utilization of industrial solid waste and reduce environmental pollution, but also effectively reduce material costs. However, steel slag itself has technical bottlenecks such as difficulty in stimulating activity and slow early strength development, which limit its promotion and application in the field of grouting materials.
[0003] Currently, some research has attempted to combine steel slag with other active materials to produce steel slag-based grouting materials. However, these materials still suffer from issues such as insufficient early strength and prolonged setting times, making them difficult to meet the engineering requirements for rapid road treatment and reinforcement. For example, in emergency repair projects, grouting materials must reach their designed strength within a short period of time to quickly restore road traffic capacity, but existing steel slag-based grouting materials often fail to meet this requirement. Furthermore, the presence of harmful components such as free calcium oxide in steel slag can lead to poor volume stability, cracking in the grouting layer, and compromising the durability of the project.
[0004] Therefore, how to provide a steel slag-based road grouting material with early strength and fast hardening to improve road maintenance and reinforcement efficiency, reduce engineering costs, and promote the resource utilization of industrial solid waste is a technical problem that technical personnel in this field urgently need to solve. Summary of the Invention
[0005] In order to solve the above technical problems, the present invention proposes an early-strengthening and fast-hardening steel slag-based road grouting material and a preparation method thereof.
[0006] To achieve the above objectives, the present invention provides the following technical solutions:
[0007] An early-strengthening and fast-hardening steel slag-based road grouting material comprises the following raw materials in parts by weight:
[0008] 60-65 parts of steel slag, 10-12 parts of fluorgypsum, 5-7 parts of slag powder, 5-8 parts of silica fume, 2-3 parts of phosphogypsum, 5.5-7.5 parts of activator, 0.2-0.3 parts of water reducer, 1-1.5 parts of expansion agent and 0.1-0.2 parts of filler.
[0009] Preferably, the stimulator comprises the following raw materials in parts by weight:
[0010] 2-2.5 parts of silicoaluminum phosphate, 3-4 parts of sodium sulfate, 4-5 parts of water glass and 0.5-0.8 parts of lithium sulfate.
[0011] Preferably, the modulus of the water glass is 1.8-2.2.
[0012] Preferably, the water reducer is a polycarboxylate water reducer.
[0013] Preferably, the expansion agent comprises the following raw materials in parts by weight:
[0014] 0.8-1.2 parts of sulphoaluminate, 0.1-0.3 parts of basalt fiber and 0.3-0.5 parts of magnesium oxide.
[0015] Preferably, the filler is nano-silicon dioxide and nano-aluminum oxide.
[0016] Preferably, the filler is a mixture of nano-silicon dioxide and nano-aluminum oxide in a ratio of (1-2):1.
[0017] Beneficial effects: The steel slag-based road grouting material provided by the present invention achieves the comprehensive advantages of early strength and fast hardening, high stability and environmental friendliness through the synergy of multiple solid wastes and component optimization. Among them, steel slag forms a sulfate-aluminate composite activation system with fluorgypsum and phosphogypsum. - Accelerate the dissolution of steel slag silicates, and phosphogypsum provides SO4 2- It promotes the formation of calcium aluminate and synergistically improves the early hydration rate; the silicoaluminophosphate and sodium sulfate in the activator activate the active ions of the steel slag, water glass adjusts the alkalinity and promotes silicate polymerization, and lithium sulfate further shortens the setting time; the expansion agent uses sulfoaluminate and magnesium oxide to form a dual expansion source, respectively achieving early and late volume compensation, and basalt fiber can inhibit cracking. In addition, nano-silica / alumina is used as a filler to optimize the pore structure, making the durability of the grouting material obtained by the present invention significantly better than that of traditional steel slag-based materials.
[0018] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material comprises the following steps:
[0019] activating the steel slag to obtain activated steel slag; mixing fluorgypsum with part of the slag powder for activation and modification to obtain activated fluorgypsum; and uniformly mixing the activated steel slag, the activated fluorgypsum, the remaining slag powder, silica fume, phosphogypsum and an expansion agent to obtain a dry material;
[0020] The exciter and water are mixed and homogenized by ultrasonication, and then a water reducer and a filler are added and dispersed evenly to obtain a wet material;
[0021] The dry material and the wet material are evenly mixed to obtain slurry, and then grouting and curing are performed to obtain the early-strength and fast-hardening steel slag-based road grouting material.
[0022] Preferably, the activation treatment of the steel slag comprises the following steps:
[0023] After the steel slag is magnetically separated and iron removed, it is ball-milled to a specific surface area of ≥450m 2 / kg, then add grinding aids and continue ball milling until the specific surface area is ≥600m 2 / kg;
[0024] More preferably, the grinding aid is citric acid, and the amount of citric acid used is 0.5-1% of the mass of the steel slag.
[0025] Preferably, the activation modification of fluorgypsum comprises the following steps:
[0026] Fluorogypsum and slag powder are mixed in a mass ratio of 3:1 and cured in a CO2 atmosphere for 24 hours to obtain activated fluorogypsum.
[0027] More preferably, the dry material and the wet material are mixed uniformly by utilizing ultrasonic homogenization and high-speed shear dispersion.
[0028] Preferably, the fluidity of the slurry is ≥300 mm.
[0029] Beneficial effect: The present invention realizes the early strength, fast hardening and high stability of steel slag-based grouting materials through multi-stage activation and process optimization. The steel slag is subjected to two-stage ball milling (specific surface area ≥ 600m 2 / kg) and combined with grinding aids, the release efficiency of active silicates is significantly improved; fluorgypsum and slag powder (3:1) are cured in a CO2 atmosphere to form a calcium carbonate coating layer, which enhances stability and promotes later hydration. The steel slag-fluorgypsum-phosphogypsum system in the raw materials forms a composite excitation of sulfate and aluminate, and the alkalinity is precisely controlled in conjunction with the activator to enable rapid polymerization of silicate, thereby improving the early strength of the product. Ultrasonic homogenization and high-speed shear dispersion in the wet mixing process can ensure the uniform distribution of nanofillers, optimize the pore structure, and greatly reduce the chloride ion permeability coefficient. The solid waste utilization rate of the entire process of the present invention is ≥90%, which greatly reduces the production cost, and the resulting grouting material has both high strength and environmental benefits.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] The present invention provides an early-strengthening and fast-hardening steel slag-based road grouting material and a preparation method thereof. Through the synergistic effect of multiple components and the optimization of the preparation process, efficient activation of steel slag and improvement of early-strengthening and fast-hardening performance are achieved, while the fluidity of the grouting material is improved, which is conducive to rapid construction and stable road structure, and promotes the resource utilization of steel slag solid waste, achieving both economic and environmental benefits. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0035] Among them, the main chemical components of steel slag include: calcium oxide (CaO): 45-55wt.%, silicon dioxide (SiO2): 15-25wt.%, ferrous oxide (FeO) and ferric oxide (Fe2O3): total iron oxide content 10-25wt.%, aluminum oxide (Al2O3): 6-12wt.%, magnesium oxide (MgO): 5-8wt.%, and the rest are other impurities.
[0036] The main chemical composition of slag powder includes: CaO: 38-45wt.%, SiO2: 28-35wt.%, Al2O3: 8-15wt.%, MgO: 5-10wt.%, and the remainder is Fe2O3 (1-3wt.%), MnO (0.5-2wt.%), TiO2 (0.3-1.5wt.%) and trace sulfides (CaS, MnS).
[0037] The modulus of water glass is 1.8-2.2.
[0038] The water reducer is a polycarboxylic acid water reducer.
[0039] Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0040] The fluidity of the slurry in the embodiments of the present invention is tested according to GB / T 2419-2005 “Determination of fluidity of cement mortar”.
[0041] Example 1
[0042] An early-strengthening and fast-hardening steel slag-based road grouting material comprises the following raw materials in parts by weight:
[0043] 63 parts of steel slag, 11 parts of fluorgypsum, 6 parts of slag powder, 7 parts of silica fume, 2 parts of phosphogypsum, 6.5 parts of activator, 0.2 parts of water reducer, 1.3 parts of expansion agent and 0.1 parts of filler.
[0044] The stimulator is obtained by mixing the following raw materials in parts by weight:
[0045] 2 parts of silicoaluminum phosphate, 3 parts of sodium sulfate, 5 parts of water glass and 0.7 parts of lithium sulfate.
[0046] The expansion agent is obtained by mixing the following raw materials in parts by weight:
[0047] 1 part of sulphoaluminate, 0.2 part of basalt fiber and 0.4 part of magnesium oxide.
[0048] The filler is obtained by mixing 0.1 parts of nano silicon dioxide and 0.1 parts of nano aluminum oxide.
[0049] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material comprises the following steps:
[0050] (1) After magnetic separation and iron removal, the steel slag is ball-milled to a specific surface area of ≥450m 2 / kg, then add 0.5% of the slag mass of citric acid as a grinding aid, and continue ball milling until the specific surface area is ≥600m 2 / kg, to obtain activated steel slag;
[0051] (2) Mixing fluorspar and slag powder in a mass ratio of 3:1 and curing in a CO2 atmosphere for 24 hours to obtain activated fluorspar;
[0052] (3) uniformly mixing the activated steel slag, activated fluorgypsum, remaining slag powder, silica fume, phosphogypsum and expansion agent to obtain a dry material;
[0053] (4) mixing the exciter and water and homogenizing them by ultrasonication, then adding a water reducer and a filler, and dispersing them evenly to obtain a wet material;
[0054] (5) The dry material and the wet material are uniformly mixed by ultrasonic homogenization and high-speed shear dispersion to obtain a slurry, so that the fluidity of the slurry is ≥300 mm, and then grouting and curing are performed to obtain a steel slag-based road grouting material with early strength and fast hardening.
[0055] Example 2
[0056] An early-strengthening and fast-hardening steel slag-based road grouting material comprises the following raw materials in parts by weight:
[0057] 60 parts of steel slag, 12 parts of fluorgypsum, 5 parts of slag powder, 5 parts of silica fume, 2 parts of phosphogypsum, 7.5 parts of activator, 0.3 parts of water reducer, 1 part of expansion agent and 0.2 parts of filler.
[0058] The stimulator is obtained by mixing the following raw materials in parts by weight:
[0059] 2 parts of silicoaluminum phosphate, 4 parts of sodium sulfate, 4 parts of water glass and 0.5 parts of lithium sulfate.
[0060] The expansion agent is obtained by mixing the following raw materials in parts by weight:
[0061] 0.8 parts of sulphoaluminate, 0.3 parts of basalt fiber and 0.5 parts of magnesium oxide.
[0062] The filler is obtained by mixing 0.1 parts of nano silicon dioxide and 0.05 parts of nano aluminum oxide.
[0063] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material comprises the following steps:
[0064] (1) After magnetic separation and iron removal, the steel slag is ball-milled to a specific surface area of ≥450m 2 / kg, then add 0.5% of the slag mass of citric acid as a grinding aid, and continue ball milling until the specific surface area is ≥600m 2 / kg, to obtain activated steel slag;
[0065] (2) Mixing fluorspar and slag powder in a mass ratio of 3:1 and curing in a CO2 atmosphere for 24 hours to obtain activated fluorspar;
[0066] (3) uniformly mixing the activated steel slag, activated fluorgypsum, remaining slag powder, silica fume, phosphogypsum and expansion agent to obtain a dry material;
[0067] (4) mixing the exciter and water and homogenizing them by ultrasonication, then adding a water reducer and a filler, and dispersing them evenly to obtain a wet material;
[0068] (5) The dry material and the wet material are uniformly mixed by ultrasonic homogenization and high-speed shear dispersion to obtain a slurry, so that the fluidity of the slurry is ≥300 mm, and then grouting and curing are performed to obtain a steel slag-based road grouting material with early strength and fast hardening.
[0069] Example 3
[0070] An early-strengthening and fast-hardening steel slag-based road grouting material comprises the following raw materials in parts by weight:
[0071] 65 parts of steel slag, 10 parts of fluorgypsum, 7 parts of slag powder, 8 parts of silica fume, 3 parts of phosphogypsum, 5.5 parts of activator, 0.2 parts of water reducer, 1.5 parts of expansion agent and 0.1 parts of filler.
[0072] The stimulator is obtained by mixing the following raw materials in parts by weight:
[0073] 2.5 parts of silicoaluminum phosphate, 3 parts of sodium sulfate, 5 parts of water glass and 0.8 parts of lithium sulfate.
[0074] The expansion agent is obtained by mixing the following raw materials in parts by weight:
[0075] 1.2 parts of sulphoaluminate, 0.1 parts of basalt fiber and 0.3 parts of magnesium oxide.
[0076] The filler is obtained by mixing 0.2 parts of nano silicon dioxide and 0.1 parts of nano aluminum oxide.
[0077] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material comprises the following steps:
[0078] (1) After magnetic separation and iron removal, the steel slag is ball-milled to a specific surface area of ≥450m 2 / kg, then add 0.5% of the slag mass of citric acid as a grinding aid, and continue ball milling until the specific surface area is ≥600m 2 / kg, to obtain activated steel slag;
[0079] (2) Mixing fluorspar and slag powder in a mass ratio of 3:1 and curing in a CO2 atmosphere for 24 hours to obtain activated fluorspar;
[0080] (3) uniformly mixing the activated steel slag, activated fluorgypsum, remaining slag powder, silica fume, phosphogypsum and expansion agent to obtain a dry material;
[0081] (4) mixing the exciter and water and homogenizing them by ultrasonication, then adding a water reducer and a filler, and dispersing them evenly to obtain a wet material;
[0082] (5) The dry material and the wet material are uniformly mixed by ultrasonic homogenization and high-speed shear dispersion to obtain a slurry, so that the fluidity of the slurry is ≥300 mm, and then grouting and curing are performed to obtain a steel slag-based road grouting material with early strength and fast hardening.
[0083] Comparative Example 1
[0084] An early-strengthening and fast-hardening steel slag-based road grouting material is different from Example 1 only in that the weight portion of steel slag is 50 parts. The remaining raw materials and preparation method are the same as those in Example 1.
[0085] Comparative Example 2
[0086] A steel slag-based road grouting material with early strength and rapid hardening is provided, which differs from Example 1 only in that fluorgypsum is not included. The remaining raw materials and preparation method are the same as those in Example 1.
[0087] Comparative Example 3
[0088] A steel slag-based road grouting material with early strength and rapid hardening is different from Example 1 only in that slag powder is not included. The remaining raw materials and preparation method are the same as those in Example 1.
[0089] Comparative Example 4
[0090] A steel slag-based road grouting material with early strength and rapid hardening is different from Example 1 only in that slag powder and fluorgypsum are not included. The remaining raw materials and preparation method are the same as those in Example 1.
[0091] Comparative Example 5
[0092] A steel slag-based road grouting material with early strength and rapid hardening is different from Example 1 only in that no filler is included. The remaining raw materials and preparation method are the same as those in Example 1.
[0093] Comparative Example 6
[0094] An early-strengthening and fast-hardening steel slag-based road grouting material, the same as that in Example 1.
[0095] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material, which differs from Example 1 only in that the activation of the steel slag in step (1) comprises the following steps:
[0096] (1) After magnetic separation and iron removal, the steel slag is ball-milled to a specific surface area of ≥450m 2 / kg, to obtain activated steel slag;
[0097] The remaining process steps and parameters are the same as those in Example 1.
[0098] Comparative Example 7
[0099] An early-strengthening and fast-hardening steel slag-based road grouting material, the same as that in Example 1.
[0100] A method for preparing an early-strengthening and fast-hardening steel slag-based road grouting material, which differs from Example 1 only in that step (2) is not included, that is, the method specifically comprises the following steps:
[0101] (1) After magnetic separation and iron removal, the steel slag is ball-milled to a specific surface area of ≥450m 2 / kg, then add 0.5% of the slag mass of citric acid as a grinding aid, and continue ball milling until the specific surface area is ≥600m 2 / kg, to obtain activated steel slag;
[0102] (2) uniformly mixing the activated steel slag, fluorgypsum, slag powder, silica fume, phosphogypsum and expansion agent to obtain a dry material;
[0103] (3) mixing the exciter and water and homogenizing them by ultrasonication, then adding a water reducer and a filler, and dispersing them evenly to obtain a wet material;
[0104] (4) The dry material and the wet material are uniformly mixed by ultrasonic homogenization and high-speed shear dispersion to obtain a slurry, so that the fluidity of the slurry is ≥300 mm, and then grouting and curing are performed to obtain an early-strength and fast-hardening steel slag-based road grouting material.
[0105] Technical effects:
[0106] The setting time of Examples 1-3 and Comparative Examples 1-7 was recorded, and the compressive strength of the grouting materials obtained in Examples 1-3 and Comparative Examples 1-7 was tested according to the standard GB / T17671-2021 "Test method for strength of cement mortar (ISO method)". The results are shown in Table 1.
[0107] Table 1
[0108]
[0109] As can be seen from Table 1, the grouting materials obtained in Examples 1-3 of the present invention have obvious characteristics of early strength and rapid hardening, and the initial setting can be completed within 60 minutes, the final setting time is also about 100 minutes, and the 24h compressive strength can reach 6.9-7.2MPa, and the 28d compressive strength can reach 37.2-40.1MPa. Comparing Example 1 of the present invention with Comparative Example 1, it can be seen that the amount of steel slag added in the present invention can significantly affect the setting time and compressive strength of the grouting material. Compared with Comparative Examples 2-4, it can be seen that there is a certain synergistic effect between the slag powder and fluorgypsum in the present invention, and the sum of the effects of the two raw materials added separately is less than the result of the two raw materials acting together. In addition, according to Comparative Examples 6-7, it can be seen that the activation treatment of steel slag and fluorgypsum in the present invention also has a significant effect on the setting time and mechanical properties of the grouting material. Comprehensive experimental data show that the technical effect of the grouting material obtained by the present invention is inseparable from the selection of raw materials and the process steps in the preparation process. The technical effect of early strength and rapid hardening can be achieved through the joint action of multiple factors.
[0110] The above are merely preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. An early-strength and fast-hardening steel slag-based road grouting material, characterized in that: The composition comprises the following raw materials in parts by weight: 60-65 parts of steel slag, 10-12 parts of fluorgypsum, 5-7 parts of slag powder, 5-8 parts of silica fume, 2-3 parts of phosphogypsum, 5.5-7.5 parts of activator, 0.2-0.3 parts of water reducer, 1-1.5 parts of expansion agent and 0.1-0.2 parts of filler.
2. The early-strength and fast-hardening steel slag-based road grouting material according to claim 1, characterized in that: The excitant comprises the following raw materials in parts by weight: 2-2.5 parts of silicoaluminum phosphate, 3-4 parts of sodium sulfate, 4-5 parts of water glass and 0.5-0.8 parts of lithium sulfate.
3. The early-strength and fast-hardening steel slag-based road grouting material according to claim 1, characterized in that: The modulus of the water glass is 1.8-2.
2.
4. The early-strength and fast-hardening steel slag-based road grouting material according to claim 1, characterized in that: The expansion agent comprises the following raw materials in parts by weight: 0.8-1.2 parts of sulphoaluminate, 0.1-0.3 parts of basalt fiber and 0.3-0.5 parts of magnesium oxide.
5. The early-strength and fast-hardening steel slag-based road grouting material according to claim 1, characterized in that: The fillers are nano silicon dioxide and nano aluminum oxide.
6. The early-strength and fast-hardening steel slag-based road grouting material according to claim 5, characterized in that: The filler is a mixture of nano silicon dioxide and nano aluminum oxide in a ratio of (1-2):
1.
7. The method for preparing the early-strength and fast-hardening steel slag-based road grouting material according to any one of claims 1 to 6, characterized in that: The following steps are involved: activating the steel slag to obtain activated steel slag; mixing fluorgypsum with part of the slag powder for activation and modification to obtain activated fluorgypsum; and uniformly mixing the activated steel slag, the activated fluorgypsum, the remaining slag powder, silica fume, phosphogypsum and an expansion agent to obtain a dry material; The exciter and water are mixed and homogenized by ultrasonication, and then a water reducer and a filler are added and dispersed evenly to obtain a wet material; The dry material and the wet material are evenly mixed to obtain slurry, and then grouting and curing are performed to obtain the early-strength and fast-hardening steel slag-based road grouting material.
8. The method for preparing an early-strength and fast-hardening steel slag-based road grouting material according to claim 7, characterized in that: The activation treatment of the steel slag comprises the following steps: After the steel slag is magnetically separated and iron removed, it is ball-milled to a specific surface area of ≥450m 2 / kg, then add grinding aids and continue ball milling until the specific surface area is ≥600m 2 / kg.
9. The method for preparing an early-strength and fast-hardening steel slag-based road grouting material according to claim 7, characterized in that: The activation modification of the fluorgypsum comprises the following steps: Fluorogypsum and slag powder are mixed in a mass ratio of 3:1 and cured in a CO2 atmosphere for 24 hours to obtain activated fluorogypsum.
10. The method for preparing an early-strength and fast-hardening steel slag-based road grouting material according to claim 7, characterized in that: The fluidity of the slurry is ≥300 mm.